2007
DOI: 10.1007/s00477-007-0198-y
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic analysis of transient three-phase flow in heterogeneous porous media

Abstract: In this manuscript, we extend the stochastic analysis of transient two-phase flow (Chen et al., Water Resour Res 42:W03425, 2006) to three-phase flow, i.e., water, air, and NAPL. We use the van Genuchten model and the Parker and Lenhard three-phase model to describe the relationships between phase saturation, phase relative permeability, and capillary pressure. The log-transformations of intrinsic permeability Y(x) = ln k(x), soil pore size distribution parameter b ow (x) = ln a ow (x) between water and NAPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Similar observations have been reported by Kueper and Gerhard (1995). Among the more recent works in this area are the researches by Zhu (2001), Chen et al (2006Chen et al ( , 2009. Zhu (2001) performed stochastic simulations to examine the effect of fractal porous media properties on the transport of NAPL in the subsurface.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar observations have been reported by Kueper and Gerhard (1995). Among the more recent works in this area are the researches by Zhu (2001), Chen et al (2006Chen et al ( , 2009. Zhu (2001) performed stochastic simulations to examine the effect of fractal porous media properties on the transport of NAPL in the subsurface.…”
Section: Introductionsupporting
confidence: 75%
“…Zhu (2001) performed stochastic simulations to examine the effect of fractal porous media properties on the transport of NAPL in the subsurface. Chen et al (2006Chen et al ( , 2009 presented stochastic numerical models based on Karhunen-Loeve expansions for two-and three-phase flow simulations, where they observed that the proposed techniques are more efficient than traditional Monte Carlo simulations presented in earlier works. In addition to forward analytical and numerical approaches, a number of inverse modeling approaches have been also presented.…”
Section: Introductionmentioning
confidence: 99%
“…Stochastic methods have been widely used in the fields of hydrology (Cantet et al 2011;Haan 1994;Lee and Yoo 2001), hydraulics (Chen et al 2009;Erik 2011;Kim et al 2004) and agriculture (Perreault et al 2000;Wu and Wang 1998;Young et al 2011). The nonlinear nature of dynamic pressure and dissipation rate is confirmed from Figs.…”
Section: Wall Shear Stressmentioning
confidence: 79%
“…This necessitates describing the conductivity and other parameters as random fields that satisfy certain statistical correlations. Many models have been developed to evaluate the uncertainty of groundwater flow and solute transport, such as the conventional Monte Carlo simulation, moment-equation method (Zhang 2002), stochastic finite element method (Ghanem 1998;Xiu and Karniadakis 2002), KLME approach (Chen et al 2009;Shi et al 2009), and stochastic collocation method (Lin and Tartakovsky 2009). The blooming of stochastic methods provide various tools for uncertainty qualification.…”
Section: Introductionmentioning
confidence: 99%